2012
DOI: 10.1177/0011128712452963
|View full text |Cite
|
Sign up to set email alerts
|

Examining Willingness to Attack Critical Infrastructure Online and Offline

Abstract: The continuing adoption of technologies by the general public coupled with the expanding reliance of critical infrastructures connected through the Internet has created unique opportunities for attacks by civilians and nation-states alike. Although governments are increasingly focusing on policies to deter nation-state level attacks, it is unclear what factors may affect citizens’ decisions to engage in politically motivated cyber crime attacks against either a foreign nation-state or their own homeland. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 51 publications
0
22
0
1
Order By: Relevance
“…Moreover, showed that differential association is a positive factor in piracy but only in low-moral-belief groups. However, a couple of studies show that negative social influence as associated with decreased piracy or positive social influence is associated with increased piracy Holt & Kilger, 2012). Finally, several studies have found no statistically significant links in either direction and thus could not make definitive conclusions or had mixed results in multiple piracy comparisons .…”
Section: Social Learning: Positive and Negative Social Influencementioning
confidence: 99%
“…Moreover, showed that differential association is a positive factor in piracy but only in low-moral-belief groups. However, a couple of studies show that negative social influence as associated with decreased piracy or positive social influence is associated with increased piracy Holt & Kilger, 2012). Finally, several studies have found no statistically significant links in either direction and thus could not make definitive conclusions or had mixed results in multiple piracy comparisons .…”
Section: Social Learning: Positive and Negative Social Influencementioning
confidence: 99%
“…A smaller percentage said they thought it would be appropriate to compromise a nuclear power plant, with 0.84% willing to attack one in their own country and 0.28% willing to attack one in a foreign country. A much larger percentage supported defacing a politician's or government website in their homeland (25.21%) or foreign country (22.40%), and still larger percentage supported posting something on Facebook (77.31% and 76.19%) [25].…”
Section: Cyber-activismmentioning
confidence: 99%
“…Even our most basic infrastructure depends on cyber systems and components that could be hacked and sabotaged with potentially large-scale, life-threatening consequences (Holt & Kilger, 2012), making hackers a primary threat to national security. There are many motivations behind hacking, including the so-called ''white hat'' motives such as increasing knowledge or improving security, ''black hat'' motives such as personal gain or retribution, and ''gray hat'' motives such as curiosity or challenge (Xu, Hu, & Zhang, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ''hacktivists'' are distinguished within the broader category of hackers by their use of technology and hacking as means to achieve political purposes or ''greater good'' (Taylor, 2005). Hacktivism is an important area of study because hacktivist motives stemming from social, political, economic, and cultural (SPEC) conflicts are increasingly cited as reasons why hacker groups plan and execute their attacks (Gandhi et al, 2011;Holt & Kilger, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation